ESRI EMEA 2010 - Leonardi, Sandra; Bartoli, Francesco (GEOmedia, 2010)
ESRI EMEA User Conference 2010 The ESRI EMEA User Conference is held every two years, and after London 2008, '2010 edition was held in Rome Oct. 26 to 28. 1500 participants from 75 countries have created one of the most important events of the GIS in which they were submitted more than 150 projects.